2013
DOI: 10.1097/coc.0b013e318248da47
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Use of Elective Mastectomy and Contralateral Prophylactic Surgery Among Breast Conservation Candidates

Abstract: In this longitudinal registry study, major independent determinants of mastectomy for early-stage breast cancer include year of diagnosis, insurance status, and stage. Mastectomy rates declined until 2004, but have since increased in conjunction with immediate reconstruction and contralateral prophylactic mastectomy. Additional study is needed to identify the underlying reasons for and unintended consequences of the reemergence of radical surgery for early-stage breast cancer in the era of multidisciplinary ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 6 publications
2
30
1
1
Order By: Relevance
“…Notably BreastScreen Australia data have also indicated higher mastectomies rates for residents of more remote areas (Cancer Australia, 2012). Large tumour sizes of 40mm or more were also predictive of mastectomy in the present study which is consistent with the higher mastectomy rates seen for larger and more advanced tumours in other studies (Lazovich et al, 1997;Taylor et al, 1999;Dragun et al, 2012b;Zorzi et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Notably BreastScreen Australia data have also indicated higher mastectomies rates for residents of more remote areas (Cancer Australia, 2012). Large tumour sizes of 40mm or more were also predictive of mastectomy in the present study which is consistent with the higher mastectomy rates seen for larger and more advanced tumours in other studies (Lazovich et al, 1997;Taylor et al, 1999;Dragun et al, 2012b;Zorzi et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…This followed other studies that indicated the potential contribution of a wide range of person, provider and cancer characteristics to choosing mastectomy (Lazovich et al, 1997;Taylor et al, 1999;Zorzi et al, 2006;Dragun et al, 2012a;2012b). Variables analysed included: 1) Age at diagnosis (<30, 30-39, 40-49, 50-59, 60-69, 70-79, 80+ years).…”
Section: Data Collectionmentioning
confidence: 99%
See 3 more Smart Citations